Effectiveness of FMCG Distribution Channels with Respect to Satisfaction of Consumers in Rural Markets - Bhoyar, Pravin Kumar; Nagendra, Asha (Indian Journal of Marketing, 2012)
Distribution is the most important variable in the marketing plans of most consumer goods manufacturers. It is estimated that there are over a million market intermediaries-distributors, super-stockists, wholesalers, stockists, transporters and retailers - who are involved in the distribution of a variety of consumer goods all over the country. This study focuses on the effectiveness of FMCG distribution channels with respect to the satisfaction of consumers in the rural market. Two companies - Hindustan Unilever Limited (HUL), and Godrej Consumer Products Limited (GODREJ), which are pioneers in Fast Moving Consumer Goods (FMCG) in the rural market were selected to study their distribution channels in 2 rural districts of Maharashtra. Two different questionnaires were designed - one for channel members, and the other for rural consumers. Results revealed that there are two distinct segments of consumers in the rural markets. One set who cannot read, write or understand with ease. They do not buy branded products. They have their own method of identification of products and communication with the retailers. Rarely do they purchase branded packaged goods. The other set was the slightly educated ones, who bought branded products and demanded range in products. The study also revealed that there were limited stocks of products at village retailers; hence, customers had to wait for some days. So, it compelled them to travel outside their villages to meet their demands. The effectiveness of FMCG distribution channels in rural markets depended upon the satisfaction of the rural customers. Since there was either poor quality or prevalence of duplicate brands in the rural market, rural customers were not getting good quality and authentic brands in the rural market of Sangli and Kolhapur districts. Hence, it was proved that the existing FMCG Channels of Distribution in Rural Maharashtra did not serve the customers well. This research was done during January 2009 and December 2009.